HUBUNGAN ANTARA OPTIMISME DENGAN FEAR OF SUCCESS PADA KARYAWAN PEREMPUAN DI PT PLN (PERSERO) UID S2JB - Dahlia Eka Tri Yuliana; Dwi Hurriyati (Media Bina Ilmiah, 2024)
This research aims to analyze the international coffee trade and provide hope for a country to overcome limited domestic savings which is the key to capital formation in order to increase economic productivity and has an important role, especially as a source of foreign exchange, providing employment opportunities and a source of income for farmers or business people. other economics related to coffee. The Indonesian government has attempted to facilitate the work or regulation of Indonesian coffee export flows by issuing regulations regarding coffee exports through Regulation of the Minister of Trade of the Republic of Indonesia Number 109 of 2018 concerning Coffee Export Provisions. Indonesia is one of the largest coffee producing countries in the world. With a large role, Indonesia is expected to be able to improve the quality of coffee in accordance with the standards set by importing countries in the international market. Therefore, there is a need for synergy with government policies that support the competitiveness of the downstream coffee industry to dominate the international market